Pneumolysin suppresses the initial macrophage pro‐inflammatory response to Streptococcus pneumoniae. Issue 3 (28th July 2022) - Periselneris, Jimstan; Turner, Carolin T.; Ercoli, Giuseppe; Szylar, Gabriella; Weight, Caroline M.; Thurston, Teresa; Whelan, Matthew; Tomlinson, Gillian; Noursadeghi, Mahdad; Brown, Jeremy
Abstract: Published data for the Streptococcus pneumoniae virulence factor Pneumolysin (Ply) show contradictory effects on the host inflammatory response to infection. Ply has been shown to activate the inflammasome, but also can bind to MRC‐1 resulting in suppression of dendritic cell inflammatory responses. We have used an in vitro infection model of human monocyte‐derived macrophages (MDM), and a mouse model of pneumonia to clarify whether pro‐ or anti‐inflammatory effects dominate the effects of Ply on the initial macrophage inflammatory response to S. pneumoniae, and the consequences during early lung infection. We found that infection with S. pneumoniae expressing Ply suppressed tumour necrosis factor (TNF) and interleukin‐6 production by MDMs compared to cells infected with ply ‐deficient S. pneumoniae . This effect was independent of bacterial effects on cell death. Transcriptional analysis demonstrated S. pneumoniae expressing Ply caused a qualitatively similar but quantitatively lower MDM transcriptional response to S. pneumoniae compared to ply ‐deficient S. pneumoniae, with reduced expression of TNF and type I IFN inducible genes. Reduction of the MDM inflammatory response was prevented by inhibition of SOCS1. In the early lung infection mouse model, the TNF response to ply ‐deficient S. pneumoniae was enhanced and bacterial clearance increased compared to infection with wild‐type S. pneumoniae . Overall, these data show Ply inhibits the initial macrophage inflammatory response to S. pneumoniae, probably mediated through SOCS1, and this was associated with improved immune evasion during early lung infection. Abstract : The Streptococcus pneumoniae cholesterol binding toxin pneumolysin has previously been shown to have both pro‐ and anti‐inflammatory effects. Here, we show that the anti‐inflammatory effects dominate during the early macrophage response to S. pneumoniae . Extracellular pneumolysin inhibits the pro‐inflammatory transcriptional response to S. pneumoniae via SOCS‐1‐mediated inhibition of NFκB translocation. This results in reduced release of TNF by macrophages, and improved immune evasion during the initial interactions of S. pneumoniae with the host in a mouse model of pneumonia.